1986
DOI: 10.1002/1097-0142(19860401)57:7<1421::aid-cncr2820570730>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrences in patients with breast cancer at the North Carolina memorial hospital (1970–1982)

Abstract: A study of predictive factors for locoregional recurrences after curative surgery for breast cancer was undertaken. Specifically, the authors wished to determine whether such recurrences correlated with either hormonal receptor status or a delay between the initial biopsy and the definitive surgery. A retrospective chart review was done on all women with breast cancer who had surgery for cure between 1970 and 1982. Factors analyzed included, among others, size of the tumor, clinical and pathologic status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 13 publications
2
7
0
2
Order By: Relevance
“…402 The frequency of local and regional recurrence for stages I and II breast cancer is clearly related to the stage of the original cancer. 403 The extent of axillary nodal involvement, specifically four or more positive nodes and extranodal extension of tumor, is a significant risk factor for locoregional recurrence. 404 Other biologic characteristics, such as hormone receptor status, 405 high-grade histologic characteristics, 406 and younger age of the patient, 407 as well as the use of adjuvant systemic therapy, are less well defined but may affect the incidence of local recurrence.…”
Section: Local Recurrence Following Mastectomysupporting
confidence: 84%
“…402 The frequency of local and regional recurrence for stages I and II breast cancer is clearly related to the stage of the original cancer. 403 The extent of axillary nodal involvement, specifically four or more positive nodes and extranodal extension of tumor, is a significant risk factor for locoregional recurrence. 404 Other biologic characteristics, such as hormone receptor status, 405 high-grade histologic characteristics, 406 and younger age of the patient, 407 as well as the use of adjuvant systemic therapy, are less well defined but may affect the incidence of local recurrence.…”
Section: Local Recurrence Following Mastectomysupporting
confidence: 84%
“…In these selected patients, we observed a local failure rate of 2.1% despite the fact that patients referred for radiotherapy have probably more often risk factors than patients treated with surgery alone. For patients with locally advanced disease, the local recurrence rate of 6.9% in our series also compares favorably to failure rates of 25% or more that have been reported in these patients with mastectomy alone in a lot of series, although some authors have observed low failure rates comparable to those in our series with additional radiotherapy [2,3,6,7,13,30,31,34,35,38]. In summary, our data are in accordance with radiotherapy results reported in recent studies which showed that radiotherapy prevents seven out of ten local recurrences that would occur without radiation therapy [8,9,24,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…268,272,277,[340][341][342][343] The risk for locoregional recurrence also rises with enlarging primary tumor size from less than 10% in patients having tumors larger than 2 cm to 25% to 35% in patients having tumors larger than 5 cm. 268,277,340,344,345,346 The risk for a supraclavicular lymph node recurrence also rises as the number of involved axillary nodes increases and may predict for distant dissemination. 339 The supraclavicular and infraclavicular regions should be included when postmastectomy radiation therapy is delivered.…”
Section: Which Patients Are At High Risk Of Locoregional Recurrence?mentioning
confidence: 99%